2016
DOI: 10.1148/radiol.2016152584
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for Predicting Pulmonary Hypertension in Patients without Pulmonary Embolism

Abstract: 327 the use of 18 F FPPRGD 2 PET as a tool to detect response to anti-angiogenesis treatment as early as 1 week after initiation of the therapeutic regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Kazakhs in Xinjiang have unique regional characteristics and special diet and living habits, which cause differences in the risk factors of hypertension. Our previous results [ 11 ] found that among Kazakh herders in Xinjiang, the factors of age, smoking, alcohol consumption, salt consumption, family history of hypertension, prehypertension, abdominal circumference, BMI, total cholesterol, triacylglycerol, and high-density lipoprotein were related to the onset of hypertension. Unhealthy lifestyles such as smoking and high salt intake could increase the risk of hypertension among Kazakh herders in pastoral areas in Xinjiang.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kazakhs in Xinjiang have unique regional characteristics and special diet and living habits, which cause differences in the risk factors of hypertension. Our previous results [ 11 ] found that among Kazakh herders in Xinjiang, the factors of age, smoking, alcohol consumption, salt consumption, family history of hypertension, prehypertension, abdominal circumference, BMI, total cholesterol, triacylglycerol, and high-density lipoprotein were related to the onset of hypertension. Unhealthy lifestyles such as smoking and high salt intake could increase the risk of hypertension among Kazakh herders in pastoral areas in Xinjiang.…”
Section: Discussionmentioning
confidence: 99%
“…Unhealthy lifestyles such as smoking and high salt intake could increase the risk of hypertension among Kazakh herders in pastoral areas in Xinjiang. [ 11 ] The dietary salt intake of most countries in the world is estimated to be 9 to 12 g/d. [ 29 ] However, the daily salt intake of the Kazakh population in the Nanshan pastoral area of Xinjiang was about 16.66 g, which is nearly 3 times the recommended salt intake of the WHO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study aimed to determine whether LODDS could be utilized to predict the cancer-specific survival (CSS) or overall survival (OS) of patients with node-positive (N1/N2 classification) LNET using the Surveillance, Epidemiology, and End Results (SEER) database. Based on LODDS, the research intended to construct two visualized and online nomograms which are practical tools for clinical prediction used in many diseases (28)(29)(30)(31)(32). To facilitate clinical use, we also constructed two visualized and online nomograms for LNETs.…”
Section: Introductionmentioning
confidence: 99%